Factors Impacting Students’ Satisfaction with Chorus Courses: A Case Study of a Comprehensive University in Guangxi, China - Wang, Huaqi (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study examines factors influencing students’ satisfaction with choir courses at a comprehensive university in Guangxi, China. Research design, data and methodology: A mixed-methods design was employed, structured across three stages: pre-IDI, IDI, and post-IDI, based on the Intervention Design and Implementation (IDI) framework. Content validity was confirmed through expert review, and a pilot test assessed reliability. Data from 90 students were analyzed using multiple linear regression to examine six factors: teachers’ competence, teaching methods, teaching staff, teachers’ reliability, learning outcomes, and helpfulness. Qualitative interviews with teachers and students informed the 12-week IDI phase. Paired-sample t-tests were conducted to compare pre- and post-intervention outcomes. Results: Teachers’ competence, teaching staff, reliability, and helpfulness significantly influenced satisfaction. Teaching methods and learning outcomes were not significant predictors. However, post-intervention results showed marked improvement across all variables, including those initially non-significant. Conclusions: The findings highlight that well-structured, student-centered interventions can meaningfully enhance student satisfaction, even for factors previously considered less impactful. This study offers practical insights for improving music education through faculty development, collaborative instruction, and support mechanisms. It also contributes to research on intervention-based approaches in arts education.